2020
DOI: 10.24179/kbbbbc.2019-72083
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Year Analysis of Publications from Turkey in the Field of Otolaryngology in Science Citation Index Journals: Before and After the Change in Criteria for Associate Professorship

Abstract: Varying criteria for associate professorship have directed researchers to write more articles and to publish in international journals. Although there have been previous studies containing evaluations of the number of citations, the current study is the first to have evaluated the number of authors and their institutions. Material and Methods: Sixteen journals in the 2018 Science Citation Index in the field of otolaryngology were examined. A record was made of which journal the article was published in, the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the study of Gokgoz et al it was shown that the articles have been written with fewer researchers with the change in the criteria for associate professorship. 6 With this study, it was seen that the new criteria cause changes in the researcher's academic behavior.…”
Section: Tablementioning
confidence: 81%
“…In the study of Gokgoz et al it was shown that the articles have been written with fewer researchers with the change in the criteria for associate professorship. 6 With this study, it was seen that the new criteria cause changes in the researcher's academic behavior.…”
Section: Tablementioning
confidence: 81%
“…Anah tar Ke li me ler: Akademik ilerleme; bibliyometrik; Türkiye; yayınlar and the number of authors. [3][4][5] In a general sense, science is a universal case and there is not expected to be a difference. The aim of this study was to compare and reveal any differences between articles written by Turkish authors in the field of otolaryngology, which have been accepted for publication in national journals in the last 6 years, and international articles in the Science Citation Index (SCI) category.…”
mentioning
confidence: 99%